Variability in Oculus Pentacam Tomographer Measurements in Patients With Keratoconus. Issue 3 (March 2015) - Vianna, Lucas M. M.; Muñoz, Beatriz; Hwang, Frank S.; Gupta, Arusha; Jun, Albert S.
Abstract : Purpose: The aim of this study was to determine intertest variability of measurements taken by the Pentacam tomographer in eyes with keratoconus. Methods: Three Pentacam measurements with 1-minute intervals were taken from 101 eyes (81 keratoconus and 20 controls) from 57 patients (47 keratoconus and 10 controls) by the same examiner and under the same conditions. Keratoconus eyes were divided into 3 subgroups based on topographic astigmatism (TA). Variability in astigmatism, mean keratometry, central corneal thickness, and fixation values were compared within the patient subgroups versus normal controls. Results: Variability of all studied parameters (astigmatism, mean keratometry, central corneal thickness, and fixation values) increased with increasing TA in patients with keratoconus. Conclusions: Pentacam measurements show increased variability in patients with keratoconus. The degree of variability correlates with TA.